Treatment of giant cell tumours of bone by radical curettage and bone cement - Medhi, Mriganka; Badole, C. M.; Mote, Girish (International Journal of Research in Medical Sciences, 2018)
Background: Giant cell tumour of bone remains a difficult and challenging management problems because there are no absolute clinical radiographic or histologic parameters that accurately predict the tendency of any single lesion to recur or metastasize. Methods: We performed surgery on 12 patients of GCT with radical curettage and bone cement over a period of 5.8 years. Results were evaluated using the musculoskeletal skeletal grading system. Results: The present series consists of 12 case of GCT age ranging from 16-45 years. Painful swelling was the commonest presentation, limitation of motion was seen in 9 cases and pathological fracture was seen in 1 case. 9 of the tumour occurred around knee joint. Rare involvement of talus was seen in 1 case. Overall 9 patients had a perfect functional score of 30 points and 1 patient scored less than 20 points. Conclusions: Acrylic cement reconstruction is safe and effective procedure that provides local adjuvant therapy, the cement field defect is mechanically stable. Patient can bear weight immediately and rehabilitate quickly.